Engineering defensin α‐helix to produce high‐affinity SARS‐CoV‐2 spike protein binding ligands. (28th May 2022) - Fernandes, Leonardo Antônio; Gomes, Anderson Albino; Guimarães, Beatriz Gomes; de Lourdes Borba Magalhães, Maria; Ray, Partha; da Silva, Gustavo Felippe
Abstract: The binding of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) spike protein to the angiotensin‐converting enzyme 2 (ACE2) receptor expressed on the host cells is a critical initial step for viral infection. This interaction is blocked through competitive inhibition by soluble ACE2 protein. Therefore, developing high‐affinity and cost‐effective ACE2 mimetic ligands that disrupt this protein–protein interaction is a promising strategy for viral diagnostics and therapy. We employed human and plant defensins, a class of small (2–5 kDa) and highly stable proteins containing solvent‐exposed alpha‐helix, conformationally constrained by two disulfide bonds. Therefore, we engineered the amino acid residues on the constrained alpha‐helix of defensins to mimic the critical residues on the ACE2 helix 1 that interact with the SARS‐CoV‐2 spike protein. The engineered proteins (h‐deface2, p‐deface2, and p‐deface2‐MUT) were soluble and purified to homogeneity with a high yield from a bacterial expression system. The proteins demonstrated exceptional thermostability (Tm 70.7°C), high‐affinity binding to the spike protein with apparent K d values of 54.4 ± 11.3, 33.5 ± 8.2, and 14.4 ± 3.5 nM for h‐deface2, p‐deface2, and p‐deface2‐MUT, respectively, and were used in a diagnostic assay that detected SARS‐CoV‐2 neutralizing antibodies. This work addresses the challenge of developing helical ACE2 mimetics by demonstrating that defensins provide promising scaffolds to engineer alpha‐helices in a constrained form for designing of high‐affinity ligands.